Defective muscle-protein biosynthesis in the hereditary cardiomyopathy of the hamster, Mesocricetus Auratus Auratus - Bester, A. J.(Andries Jacobus) (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph.D.(Med.)) -- University of Stellenbosch, 1973.